Endovascular stenting of the inferior vena cava in a patient with Budd-Chiari syndrome and main hepatic vein thrombosis: a case report - Yoon, Young-In (Korean J Hepatobiliary Pancreat Surg, 2015)
Endovascular stenting is accepted as an effective treatment for patients with Budd-Chiari syndrome (BCS). We herein present a case of successful endovascular treatment. A 46-year-old woman, who was followed up for 10 years after a diagnosis of BCS, showed progression progressive of liver cirrhosis and deterioration deteriorated of liver function. Three main hepatic veins were thrombosed with complete occlusion of the suprahepatic of the inferior vena cava (IVC); thus, hepatic venous blood flow was draining into the inferior right hepatic veins through the intrahepatic collaterals and passed passing through the subcutaneous venous collaterals. She underwent endovascular stenting of the IVC for palliation. A septoplasty needle was passed through the occluded IVC through into the internal jugular vein access and then to access the femoral vein using a snare wire. Severe elastic recoiling was observed after balloon dilatation; thus, a 28×80 mm stenting was done inserted across the occlusion, and repeat double ballooning was performed. The final venogram shows showed restored IVC inflow. The patient began to lose body weight 1 day after stenting, and edema disappeared within 1 week. She is was doing well at the 6 month follow-up visit with nearly normal liver function and marked resolution of cutaneous venous engorgement. In conclusion, endovascular stenting appeared to be an effective treatment to alleviate portal pressure and to prevent BCS-associated complications; thus, endovascular stenting should be considered before marked hepatic vein stenosis or complete occlusion occurs in patients with BCS.